2020
DOI: 10.1136/archdischild-2019-317720
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic hydrocortisone in extremely preterm infants and brain MRI abnormality

Abstract: ObjectiveTo determine whether early low-dose hydrocortisone treatment in extremely preterm infants is associated with brain damage assessed by MRI at term equivalent of age (TEA).Patients and outcomesThis is a predefined secondary analysis of brain abnormalities, observed by MRI at TEA, of patients randomly assigned to receive either placebo or hydrocortisone in the PREMILOC trial. Outcomes were based on brain abnormalities graded according to Kidokoro scores.ResultsAmong 412 survivors at TEA, 300 MRIs were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…It is possible that, as was theorized by the PREMILOC study team, lowdose hydrocortisone may not cause alterations to oligodendrocyte precursor cell development in the same way that more potent and high-dose glucocorticoids do. 7,9,34 This explanation is consistent with recent research looking at brain outcomes related to hydrocortisone treatment. Studies looking at macroscopic brain injuries (PVL, IVH, brain lesions) and brain volume have indicated that hydrocortisone was not associated with adverse effects on brain, in contrast to the reduced brain volume and increased brain abnormalities seen with dexamethasone.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is possible that, as was theorized by the PREMILOC study team, lowdose hydrocortisone may not cause alterations to oligodendrocyte precursor cell development in the same way that more potent and high-dose glucocorticoids do. 7,9,34 This explanation is consistent with recent research looking at brain outcomes related to hydrocortisone treatment. Studies looking at macroscopic brain injuries (PVL, IVH, brain lesions) and brain volume have indicated that hydrocortisone was not associated with adverse effects on brain, in contrast to the reduced brain volume and increased brain abnormalities seen with dexamethasone.…”
Section: Discussionsupporting
confidence: 89%
“…Studies looking at macroscopic brain injuries (PVL, IVH, brain lesions) and brain volume have indicated that hydrocortisone was not associated with adverse effects on brain, in contrast to the reduced brain volume and increased brain abnormalities seen with dexamethasone. 6,7,12 Several limitations constrain interpretation of our findings. Infants were not randomized to control or treatment groups, but rather received the treatment as a function of timing of birth.…”
Section: Discussionmentioning
confidence: 87%
“…Compared to a previous study that was stopped prematurely because of the increase in the frequency of GI perforation, the PREMILOC trial showed no increase in GI or other short-term complications, and the long-term neurodevelopmental outcomes were also similar, or even improved in extremely preterm infants [102,103]. In addition to the clinical prognosis, the PREMILOC study also evaluated the hydrocortisone effect on brain structure by assessing brain MRI at term equivalent of age and concluded that neither white matter brain damage nor overall moderate-to-severe brain lesions were statistically different among those who had early hydrocortisone exposure when adjusted for other neonatal variables [104]. The exposed infants should have a neurodevelopment assessment at preschool age to verify the safety of early hydrocortisone because re-evaluation at this age reflects a child's general intellectual ability more accurately [105].…”
Section: Hydrocortisonementioning
confidence: 99%
“…Allison et al (Alison M et al, 2020) conducted a large predefined secondary analysis of T1, T2, T2 GE MRI at term equivalent age of patients enrolled in the PREMILOC trial of early hydrocortisone. A standardized scoring system was used to evaluate cerebral WM, cortical and deep GM and cerebellar abnormalities.…”
Section: Resultsmentioning
confidence: 99%